EVALUATION OF DRAINAGE CHANNEL CAPACITY ON JALAN BUDI KARYA, PONTIANAK SELATAN SUB-DISTRICT - Suci, Suci; Herawati, Henny; Umar, Umar; Soeryamassoeka, SB; Gunarto, Danang (Fakultas Teknik Universitas Tanjungpura, 2022)
Drainage is one of the most critical components to be maintained and developed in a strategically healthy and comfortable urban environment. There are often puddles of water on Budi Karya Street, especially at the Permai Reservoir Complex. In solving the existing inundation problem, primary and secondary data are needed. Primary data is in the form of longitudinal and transverse sections of the channel, while secondary data is in the form of location maps, tidal data, and rainfall data used to analyze hydrology. Based on the analysis of the capacity of Budi Karya's drainage channel using HEC -RAS software as a drainage channel flow modeling tool to view the water level profile along the channel, channel perspective drawing, or hydrograph, it was found that the Budi Karya drainage channel could not accommodate the planned discharge for return periods 2 and 5 Year. Therefore, it is necessary to improve drainage in the form of the normalization of drainage channels.